2012
DOI: 10.1093/nar/gks409
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel NRF2-regulated genes by ChIP-Seq: influence on retinoid X receptor alpha

Abstract: Cellular oxidative and electrophilic stress triggers a protective response in mammals regulated by NRF2 (nuclear factor (erythroid-derived) 2-like; NFE2L2) binding to deoxyribonucleic acid-regulatory sequences near stress-responsive genes. Studies using Nrf2-deficient mice suggest that hundreds of genes may be regulated by NRF2. To identify human NRF2-regulated genes, we conducted chromatin immunoprecipitation (ChIP)-sequencing experiments in lymphoid cells treated with the dietary isothiocyanate, sulforaphane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
441
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 489 publications
(471 citation statements)
references
References 108 publications
(118 reference statements)
27
441
3
Order By: Relevance
“…Surprisingly, however, treatment of these lymphoblastoid cells with the NRF2-activating compound sulforaphane resulted in a downregulation of mature miR-29b (ref. 14). The discrepancy to our results obtained in keratinocytes may result from NRF2-independent effects of sulforaphane on expression/maturation of miR-29 (ref.…”
Section: Discussioncontrasting
confidence: 76%
See 2 more Smart Citations
“…Surprisingly, however, treatment of these lymphoblastoid cells with the NRF2-activating compound sulforaphane resulted in a downregulation of mature miR-29b (ref. 14). The discrepancy to our results obtained in keratinocytes may result from NRF2-independent effects of sulforaphane on expression/maturation of miR-29 (ref.…”
Section: Discussioncontrasting
confidence: 76%
“…Another NRF2 ChIP-Seq study using human lymphoblastoid cells confirmed the genome-wide distribution of NRF2 binding in the vicinity of miRNA genes and found a peak of NRF2 binding in the upstream region of the human MIR29AB1 cluster 14 . Surprisingly, however, treatment of these lymphoblastoid cells with the NRF2-activating compound sulforaphane resulted in a downregulation of mature miR-29b (ref.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…A recent study using chromatin immunoprecipitation sequencing (ChIP-Seq) identified high-confidence ChIP-Seq peaks for NRF2 binding in the vicinity of several miRNAs, suggesting they could be regulated by NRF2. 15 In the present study, we look to identify whether NRF2 regulates miRNA in human AML. Furthermore, we evaluate whether NRF2-regulated miRNAs have functional importance not only on the biology of the disease but also in the leukaemia cell death to chemotherapy treatment.…”
mentioning
confidence: 99%
“…[19][20][21][22][23] Nrf2 can directly bind and activate adipogenic genes such as peroxisome proliferator-activated receptor γ (Pparγ) 21 and retinoid X receptor α (RXRA). 24 Nrf2 controls hematopoietic stem cell functions through transcriptional regulation of CXCR4. 22 In mouse liver, Nrf2 activates small heterodimer partner (SHP) nuclear receptor and lipid metabolism genes.…”
Section: Regulation Of Developmentalmentioning
confidence: 99%